O tio de inglês nos meandros da autoetnografia: decolonialidades e representatividades por meio do trabalho com material didático - Santos, Douglas Freitas dos (2024)
In public regular schools, the teaching and learning of the English Language on all levels of Basic Education is already a reality in many Brazilian cities. This means that Brazilian students might have access to the English Language in classroom since the first year of Elementary School to the last grade of High School. Nonetheless, there is an absence of guidelines when it comes to the discipline in the Brazilian Common Core Curriculum. Besides this gap, there are other problems, such as the absence of institutional adoption of an English textbook to early years. Such implication may have diverse consequences to the teaching and learning of English. One of these consequences is an overload of work to teachers who deal with other contexts and do not have resources, time, or education that overcome the prominent gap. Another consequence is the autonomous adoption, by teachers, of teaching materials and other resources that, because are not chosen critically in a collective manner, may either be of poor quality or prejudicial. Considering the scenario described, this study aims to reflect on how decolonialities and representations are part of my work as a teacher and teaching material designer for the discipline of the English Language of early years in Elementary School. To do so, I consider, besides the teaching materials used and my work from them, some scenes that reflect my processes of teaching and learning of English since the time of being a language student in a private course. In this regard, this study is under the principles of autoethnography as methodology (Ono, 2018). Thus, through reflection and analysis of my experiences with the themes aforesaid, regarding data obtained from personal records, narratives, lesson plans, among others, I aim to discuss the role of teaching material in a scenario dominated by uncertainties. In that regard, I highlight the relevance of studies that emphasize the urgency of being aware of colonialities in education and how teaching materials can contribute to the development of that awareness. This process may lead us to more decolonial, transforming, and critical paths.